2017
DOI: 10.1128/aem.02702-16
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rhamnose-Rich Hetero-exopolysaccharide Isolated from Lactobacillus paracasei DG Activates THP-1 Human Monocytic Cells

Abstract: Lactobacillus paracasei DG is a bacterial strain with recognized probiotic properties and is used in commercial probiotic products. However, the mechanisms underlying its probiotic properties are mainly unknown. In this study, we tested the hypothesis that the ability of strain DG to interact with the host is at least partly associated with its ability to synthesize a surface-associated exopolysaccharide (EPS). Comparative genomics revealed the presence of putative EPS gene clusters in the DG genome; according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 52 publications
8
75
0
6
Order By: Relevance
“…44,45) The present study shows that the IC 50 value for the SN35N-derived acidic EPS to hyaluronidase has almost the same as those of sodium cromoglicate and dipotassium glycyrrhizinate used as an anti-inflammatory agent (hyaluronidase inhibitors). 45,46) Interestingly, although our previous report has showed that the neutral EPS produced by P. pentosaceus LY45 inhibits hyaluronidase activity more effectively than did the acidic EPS, including fucoidan. 22) The IC 50 value of the SN35N-derived acidic EPS is significantly lower than those of the acidic ones.…”
Section: Eps-biosynthesizing Gene Cluster Detected In the Lb Plantarmentioning
confidence: 91%
See 1 more Smart Citation
“…44,45) The present study shows that the IC 50 value for the SN35N-derived acidic EPS to hyaluronidase has almost the same as those of sodium cromoglicate and dipotassium glycyrrhizinate used as an anti-inflammatory agent (hyaluronidase inhibitors). 45,46) Interestingly, although our previous report has showed that the neutral EPS produced by P. pentosaceus LY45 inhibits hyaluronidase activity more effectively than did the acidic EPS, including fucoidan. 22) The IC 50 value of the SN35N-derived acidic EPS is significantly lower than those of the acidic ones.…”
Section: Eps-biosynthesizing Gene Cluster Detected In the Lb Plantarmentioning
confidence: 91%
“…Furthermore, it has been shown that some Lactobacillus strains, such as Lb. paracasei DG, 47) Lb. casei YIT9018, 48) and Lb.…”
Section: Eps-biosynthesizing Gene Cluster Detected In the Lb Plantarmentioning
confidence: 99%
“…The monosaccharides present were determined after acid hydrolysis either directly using HPAEC-PAD analysis or as their alditol acetates, as previously described(12). The absolute configuration of the sugars was determined by preparation of their respective 2-( S )-butylglycosides using Gerwig’s method(52).…”
Section: Methodsmentioning
confidence: 99%
“…The strain produces significant quantities of a mixture of EPS (∼2g/L) and it has been demonstrated that the crude EPS has immunomodulatory activity (11). In previous studies, using EPS from lactic acid bacteria (12; 13), we have shown that specific EPS can stimulate production of pro- and anti-inflammatory cytokines. We also provided evidence that the EPS can modulate the immune response and in doing so provide a degree of immunotolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies revealed that exopolysaccharides (EPS) could modulate the immune system. A previous study fully elucidated that a novel rhamnose‐rich heteroexopolysaccharide isolated from L. paracasei DG may activate human monocytic cells by increasing the gene expression of proinflammatory cytokines combined with chemokine (C‐C motif) ligand 20 (CCL20) (Balzaretti et al, ). By contrast, Vinderola, Perdigon, Duarte, Farnworth, and Matar () revealed that exopolysaccharide extracted from L. kefiranofaciens strengthened intestinal mucosal immunity through increasing IgA+ cells, leading to enhancement of IgA production (Vinderola et al, ).…”
Section: Regulatory Effects Of Probiotics On the Immune Systemmentioning
confidence: 99%